The literariness of travel literature: the horizons of perspective and vision - doghmane, ali (El Omda in Linguistics and Discourse Analysis, 2023)
The present study seeks to formulate a concept specific to travel literature in a way that focuses on its nature rather than its definition, function, or purposes. This places us in confrontation with its techniques as possible manifestations that reflect its literariness, while also allowing it to distinguish itself from other literary genres. This, in turn, leads to questioning traditional critical theory in search of the horizons of travel literature, alongside critical approaches concerned with examining its aesthetic and artistic conventions. This has been achieved through a close examination of the two terms in sequence: “literature” and “travel,” which, through the accumulation of partial conceptions resulting from the continuous process of deconstruction and reconstruction, has led to defining a concept specific to this fluid literary genre, and consequently reordering it within the hierarchy of literariness in line with its new status.